Analysis of 6-Pulse and 12-Pulse in Conversion of the 115VAC/400Hz to 270 VDC for Application on Fighter - Dwi Rochma Agustiningsih, Edy Suwondo, Muhammad Kusni (Institut Teknologi Bandung, 2019)
The development of aircraft secondary power technology is moving from mechanical power, pneumatic power and hydraulic power to electric power. The trend toward electric power is known as More Electric Aircraft (MEA). Modern military aircraft are designed using 270VDC for electric power system. Today, some military aircraft still use 115VAC/400Hz for their electrical power system. If this type of aircraft need provides 270VDC electrical power, then they require Multi-Pulse Transformer Rectifier Unit (TRU). The development of this type TRU has not been aimed to comply with aircraft military standards. This research investigates the variation of the number of pulses (p) and firing angle (α) to the amplitude ripple voltage, output voltage, and distortion factor in order to comply with the MIL-STD-704F standards. The multi-pulse transformer rectifier unit being analyzed consists of 6-Pulse and 12-Pulse. The research shows that the amplitude ripple voltage and distortion factor of the 6-Pulse TRU do not comply MIL-STD-704F. The amplitude ripple voltage and distortion factor of 12-Pulse comply MIL-STD-704F with firing angle (α) ≤4°.Keywords: Transformer Rectifier Unit, thyristor, ripple voltage, distortion factor, firing angle